2008
DOI: 10.1158/1078-0432.ccr-07-4820
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Invasion and Metastasis of Hepatocellular Carcinoma Cells via Targeting RhoC In vitro and In vivo

Abstract: Purpose: Hepatocellular carcinoma (HCC) is one of the most deadly human cancers because of its high incidence of metastasis. Our previous work identified a strong correlation between increased expression of RhoC and HCC metastasis. Here, we investigate to define the role of RhoC in HCC metastasis. Furthermore, we sought to determine whether inhibition of the expression of RhoC might block the metastasis of HCC in vivo. Experimental Design: A stable retroviral small interfering RNA approach was employed to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…Metastasis, the final step of neoplastic progression, remains the major cause of death from HCC (Wang et al 2008; Winnard et al 2008). Still, the environmental risk factors for HCC metastasis are not clearly known (Uka et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis, the final step of neoplastic progression, remains the major cause of death from HCC (Wang et al 2008; Winnard et al 2008). Still, the environmental risk factors for HCC metastasis are not clearly known (Uka et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, YMO1 didn't increased ubiquitination of RhoC (Supplementary Figure S8). Our previous study has indicated that RhoC expression was remarkably increased in HCC tissues and was associated with metastasis of HCC [21]. Rho-GTPases, members of Ras superfamily of small GTPases, shuttle between inactive GDP-bound and active GTP-bound form and exhibit intrinsic GTPase activities [22].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, RhoC has emerged as a key factor in tumor progression in many types of cancer that include invasive breast carcinoma (5,15), gastric cancer (13), non small cell lung carcinoma (14), ovarian carcinoma (8), and esophageal squamous cell carcinoma (70). In addition, RhoC has been shown to be essential for metastasis in animal models (10,11,12,72).…”
Section: Discussionmentioning
confidence: 99%